2018
DOI: 10.1038/s41524-018-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying quasi-2D and 1D electrides in yttrium and scandium chlorides via geometrical identification

Abstract: Developing and understanding electron-rich electrides offers a promising opportunity for a variety of electronic and catalytic applications. Using a geometrical identification strategy, here we identify a new class of electride material, yttrium/scandium chlorides Y(Sc) x Cl y (y:x < 2). Anionic electrons are found in the metal octahedral framework topology. The diverse electronic dimensionality of these electrides is quantified explicitly by quasi-two-dimensional (2D) electrides for [YCl] + •e − and [ScCl] + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 77 publications
2
58
0
Order By: Relevance
“…It was recently reported that the layer structured [Ca 2 N] + •e − electride showed an extremely high mobility as well as distinct anisotropic properties in electrical transport and work function, which were ascribed to the fully delocalized high-density IAEs (1.39 × 10 22 cm −3 ) confined in two-dimensional (2D) interlayer space. The layer structured [Ca 2 N] + •e − electride was referred to as "2D electride" 8 , triggering the development of various 2D electrides [11][12][13][14] .…”
mentioning
confidence: 99%
“…It was recently reported that the layer structured [Ca 2 N] + •e − electride showed an extremely high mobility as well as distinct anisotropic properties in electrical transport and work function, which were ascribed to the fully delocalized high-density IAEs (1.39 × 10 22 cm −3 ) confined in two-dimensional (2D) interlayer space. The layer structured [Ca 2 N] + •e − electride was referred to as "2D electride" 8 , triggering the development of various 2D electrides [11][12][13][14] .…”
mentioning
confidence: 99%
“…The identified electrides show a lot of variability in their chemical composition and crystal packing, demonstrating the power of HT methods to discover novel electride. Extending this search to more materials (e.g., inorganic wide-gap semiconductors 57 , insulators and organic compounds 37 ) would be the subject of future work. In addition, we believe that the descriptor proposed in this work can be also used to identify the electride materials from more extended first-principles crystal structure search 14,18 .…”
Section: Resultsmentioning
confidence: 99%
“…It seems that, for this family of carbides, carbon has the propensity to alter its structural unit to offer a variety of stable compounds, [ 29,30 ] and even open up band gaps in non‐octet compounds akin to multivalent 3 d transition elements that form Mott and charge transfer insulators. The gapped systems Sc 3 C 4 and Sc 2 C also have isotypic compounds with similar properties, M 3 C 4 (with M=Y, La, Lu, Tm, Ho [ 31–33 ] ) and M 2 C (with M = Y, La [ 21–25 ] ), and we find that also the isotypic MXene systems M 2 CO 2 with (with M=Y, La, Lu, Tm, Ho) in our newly discovered rhombic structure with C 3 structure units (C 3 ‐M 2 CO 2 ) are electrides, and significantly more stable than their respective hexagonal MXene phases (hex‐M 2 CO 2 or AFE‐M 2 CO 2 ).…”
Section: Introductionmentioning
confidence: 52%
“…This kind of behaviour indicates that the systems are electrides. [ 33,51–56 ]…”
Section: Resultsmentioning
confidence: 99%